THE REFLECTIONS OF FAIRNESS WITHIN THE SPHERE OF CONTEMPORARY TAXATION - Dimitrijević, Marina (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The fairness of taxation represents one of the inevitable topics in the domain of evaluating the effects of taxation within the national framework. The path towards achieving fair taxation is burdened by many obstacles, particularly expressed in the time of complex and changing socio-political and economic trends. Each period has its own traps, and therefore, full content, true meaning and factual acceptance of the postulate of fair taxation needs to be examined constantly. In that sense the fairness of taxation and its reflections in the sphere of contemporary taxation are the subject of examination in this paper. Taking into consideration that fair taxation is a reliable support for building correct tax-law relations, a detailed analysis of fundamental requirements for its implementation, expressed in the form of generality of tax obligation (tax universality) and equal distribution of tax load, has been done. Therefore, special attention is paid to explaining the occurrence of a relatively limited effect of the generality of tax obligation in contemporary conditions, which causes the existence of tax exemption and tax reliefs, as well as the explanation of dimensions of horizontal and vertical equity in taxation. The paper also reviews in detail transformations of tax systems, achieved as the result of conducted tax reforms during several previous decades, with the aim of confirming the hypothesis about the weakened significance of the ability to pay principle (the principle of paying taxes according to economic faculty) as a fundamental rule for modelling contemporary tax structures.